A Case of Monochorionic-Triamniotic Triplet Pregnancy with TRAP Sequence Successfully Treated with Radiofrequency Ablation with a Parallel Circuit Consisting of Anastomosed Blood Vessels between the Direct Pump Fetus and the Indirect Pump Fetus - Shusaku Kobori; Masatake Toshimitsu; Shinichi Nagaoka; Jun Murotsuki (Case Reports in Obstetrics and Gynecology)
Monochorionic-triamniotic triplet pregnancy with twin reversed arterial perfusion (TRAP) sequence is one of the rare complications of multiple pregnancy and has been reported by only a few. Here, we report a case of monochorionic-triamniotic triplet pregnancy with TRAP sequence successfully treated with radiofrequency ablation, which did not develop polyhydramnios and heart failure although the estimated weight of the acardiac fetus increased twice as much as that of the direct pump fetus. Interestingly, the anastomosed blood vessels between the direct and indirect pump fetuses comprised a parallel circuit, which provided blood flow to the acardiac fetus. We hypothesized that the burden on the pump fetus in monochorionic pregnancy with TRAP sequence would be different between triplet and twin pregnancies.